Physicochemical and technological properties of water-soluble extracts from germinated yellow corn - Andressa, Irene; do Nascimento, Glauce Kelly Silva; Teotônio, Daniela de Oliveira; Neves, Nathália de Andrade; Benassi, Vivian Machado; Schmiele, Marcio (Revista Principia, 2025)
Lactose intolerance affects approximately 70% of the global population, leading to increased demand for alternative raw materials and technologies that enhance the nutritional and functional properties of plant-based beverages. In this context, the present study investigates the development of water-soluble extracts from germinated yellow corn, aiming to improve their physicochemical and technological properties for a possible use as a plant-based beverage. The effects of germination time and temperature on the physical and physicochemical characteristics of yellow corn grains and their corresponding water-soluble extracts were evaluated. The results demonstrated significant variations in soluble solids content, particularly in assays with prolonged germination times and elevated temperatures (32 °C for Assays 2 and 5), which are attributed to increased endogenous enzymatic activity. The rise in soluble solids suggests an increase in reducing carbohydrates due to starch hydrolysis, contributing to enhanced colloidal stability. Furthermore, modifications in color parameters (L*, a*, b*) were observed in both germinated corn flours and their water-soluble extracts, influenced by enzymatic activity and processing conditions. These findings indicate that water-soluble extracts from germinated yellow corn could serve as viable alternatives to plant-based products, thereby reducing the need for added sucrose and chemical additives.